Blood Biochemicals of Broiler Chickens after Been Fed Cassia obtusifolia Seed Meal - Neils , J.S.; Augustine, C.; Mojaba, D.I.; Dazala, U.I. (International Journal of Poultry Science, 2013)
The effect of processed Cassia obtusifolia seed meal as a replacement of protein on blood biochemistry (protein, albumin, globulin, Creatinine and cholesterol) was studied. One hundred and twenty (120) day old broilers chicks purchased from reputable source were randomly divided into four dietary treatments in a Randomized Complete Block Design (RCBD) with three replicates of ten birds each. Four experimental feeds were compounded with processed Cassia obtusifolia seed meal as replacement for protein at concentrations of 0, 2.5, 5.0 and 7.5% inclusion. The groups are as T1, T2, T3 and T4 groups, respectively, where T1 served as control. The experimental diet was fed to the birds for a period of 8 weeks. T2 (2.5%) and T3 (5.0%) groups had normal blood biochemical parameters while T4 (7.5%) did give normal range of biochemical values except for cholesterol level (172.86mg). The increase showed a level of significance (P